Differentiation of personal income by the autonomous regions of Spain - I. V. Mitroshin (Управление)
Average per capita income of the population is one of the important indicators reflecting the standard of living in the country. It becomes relevant to determine reasons for differentiating income per capita and per household and to identify the causes that affect it. The paper considers the income of the population in the autonomous regions of Spain for 2008–2021 both per capita and per household. A comparative analysis of incomes with and without imputed rents has been carried out, that is, the share of rental expenditure in household income and the trend in its change over the last thirteen years have been determined. The results of the study revealed higher living standards in some industrialized regions of the North of the country, such as Navarra and the Basque Country, as well as in regions where large metropolitan areas are located. These are the Autonomous Region of Madrid with a population of 6.7 million people (directly Madrid – about 5 million people) and Catalonia with a population of 7.7 million people with the administrative center in Barcelona (4.5 million people). Slow growth of citizens’ expenditures on rental housing has also been revealed. Due to growing individualization of the population and reduction of the number of people in a family, the number of people in one household is decreasing on average in the country. The analysis of population change in Spain shows that the demographic situation remains positively stable. In general, there is population growth, but depopulation is occurring in the interior regions of the country, such as Extremadura, Castile-La Mancha, Castile and Leon, Aragon. In addition to living standards, other factors such as climate, proximity to the coast, and tourist attractiveness have an impact on migration processes.